Technical performance in elite women`s Australian football - comparisons with men`s football, identifying important performance characteristics and apparent trends - Dwyer, D. B.; Domenico, I. D.; Young, C. M. (International Journal of Performance Analysis in Sport, 2022)
There is a need to establish normative values for technical performance indicators (PI) in the relatively new Australian Football League Women`s (AFLW), to identify trends, to compare with the established men`s league, and associations with match outcome. Data from the 2019 AFL (men`s) season and the 2017-19 AFLW (women`s) seasons, included the normalised (to 60 minute) match totals for 23 technical PIs and five score-based PIs. The values of 23 PIs were different (p < 0.05) between the women`s and men`s leagues. These differences suggest that women make fewer disposals (passes) to teammates, they make more errors and contest possession of the ball more often. Consequently, AFLW teams move the ball to within 50 metres of their goal and score less often. There are eight PIs that appear to be on a trend of increase in the AFLW. The relationships between the characteristics of team technical performance and match outcome are similar between the leagues, although contested possession is more important in the AFLW. Technical performance of the athletes in the women`s league is different to men, but some of these differences appear to be narrowing. Despite the differences, the relationship between technical performance and match outcome are similar in both leagues.